2019
DOI: 10.3390/ijgi8050211
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Mapping of Rice Cropping Pattern in Flooding Area in the Vietnamese Mekong Delta Using Sentinel-1A Data: A Case of An Giang Province

Abstract: Cropping intensity is one of the most important decisions made independently by farmers in Vietnam. It is a crucial variable of various economic and process-based models. Rice is grown under irrigated triple- and double-rice cropping systems and a rainfed single-rice cropping system in the Vietnamese Mekong Delta (VMD). These rice cropping systems are adopted according to the geographical location and water infrastructure. However, little work has been done to map triple-cropping of rice using Sentinel-1 along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 71 publications
1
43
0
1
Order By: Relevance
“…Although As concentration in An Giang was under the permissible limits of the National technical regulation on groundwater quality (0.05 mg/L) since 2014, it still exceeds the WHO permissible limit of 0.01 mg/L [50]. There is insufficient evidence to conclude whether agricultural activity affects aquifer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although As concentration in An Giang was under the permissible limits of the National technical regulation on groundwater quality (0.05 mg/L) since 2014, it still exceeds the WHO permissible limit of 0.01 mg/L [50]. There is insufficient evidence to conclude whether agricultural activity affects aquifer.…”
Section: Discussionmentioning
confidence: 99%
“…An Giang province is part of the agricultural intensification region of the VMD, where the water regime is mainly under human control through sluice gates, canals, and dike systems [47][48][49]. The land use/land cover (LULC) map of An Giang shows the percentage of various LULC classes in 2018 with a triple, double, and single rice crop, and other classes that cover 46.6%, 24.7%, 7.3%, and 21.4%, respectively [50]. The highly irrigated triple and double rice crops occur inside the dike system using surface water, which has negative impacts on surface and groundwater quality especially in the full-dike system [29,46].…”
Section: Study Areamentioning
confidence: 99%
“…The high nutrients in the dry season can be attributed to the wastewater that is discharged directly into the canal system from fishponds on secondary canals, as well as from households, markets, and tourists on primary canals. Moreover, people often live along the riverbanks of primary canals and rely on them for their livelihoods, while farmers often construct minor canals (or ditches) for irrigation and drainage from their rice fields [39]. Thus, the fresh water resources inside the dike system were not very suitable for aquatic life.…”
Section: Discussionmentioning
confidence: 99%
“…This first continental-scale, multi-decadal assessment of annual mangrove distribution showed that mangrove forest extent in Australia peaked in 2010 and has since declined by about 240 km 2 [139]. Several recent studies have used Sentinel-1 SAR time series data to map the distribution of rice paddies and aquaculture ponds in river deltas, taking advantage of the unique seasonal inundation dynamics and microwave backscattering characteristics of these features [171,172,[188][189][190]. Advances in SAR-based mapping of aquaculture ponds are already covered in the previous chapter, and therefore, are not repeated here.…”
Section: Earth Observation Potential For Land Cover and Land Use Infomentioning
confidence: 99%